(3GdYQhb GdgfOjI GdeSeGI HGdYTHIs - (3GdUbdjs
(3ChdgG (B:s
(3GYde Cf GdGhGFd de jPcQhG gPg GdYQhb , hEfeG XgQJ HGdeZQH efP KdGKjf SfI, jYfi HCQV GdeZQH , heGCgd GdeTQb adG jYdehf dgG ESekG ef CMO ef GdbOeGA s
(3BNQgG (B:s
(3hCeG GdOgf adG jbQHg EdG YGde YGQa, Ch eZQQ HGdfGS , Ch LGgd aGLQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B156 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B800) s
Keywords: (3GdWHs